RoHS regulated Substances in Mixed Plastics from Waste Electrical and Electronic Equipment - Wäger, Patrick A; Schluep, Mathias; Müller, Esther; Gloor, Rolf (Environmental science & technology, 2012)
The disposal and recovery of plastics from waste electrical and electronic equipment (WEEE) are of considerable importance, both from an environmental and an economic perspective. This paper presents the results of a study investigating current concentrations of hazardous substances in mixed plastics from WEEE and their implications for an environmentally sound recovery. The study included 53 sampling campaigns for mixed plastics from WEEE. The samples were analyzed with regard to heavy metals (cadmium, chromium, mercury, and lead) and flame retardants (PentaBDE, OctaBDE, DecaBDE, DecaBB) regulated in the RoHS Directive. Besides these substances, other brominated flame retardants known to occur in electronics (HBCD, TBBPA) as well as the total bromine and phosphorus contents were considered. Results show that no mixed plastics fraction from WEEE is completely free from substances regulated in the RoHS Directive. The lowest number and average concentrations were found in flat screen monitors. The highest concentrations were found in mixed plastics from CRT monitors and TVs. Mixed plastics fractions with high average concentrations of heavy metals originate from the treatment of small household appliances (cadmium), ICT equipment (lead), and consumer equipment (lead). Mixed plastics fractions with high average concentrations of brominated flame retardants mainly originate from the treatment of small household appliances for high temperature applications (DecaBDE), CRT monitors (OctaBDE and DecaBDE) and consumer equipment (DecaBDE), in particular CRT TVs (DecaBDE). To avoid a dissipation of hazardous substances into plastics and the environment, it is recommended that mixed plastics from WEEE are subject to a strict quality management.